The Final Years of Central State Hospital. (18th October 2018) - Dwyer, Ellen
Abstract: There is a rich literature on the deinstitutionalization movement in the US but few, if any, parallel histories of state mental hospitals. Under attack from the 1950s on, state hospitals dwindled in size and importance. Yet, their budgets remained large. This paper offers a case study of one such facility, Indiana's Central State Hospital, between 1968 and 1994. During these years, local newspapers published multiple stories of patient abuse and neglect. Internal hospital materials also acknowledged problems but offered few solutions. In 1984, the US Department of Justice intervened, charging Central State with having violated patients' civil rights, the first such action filed under the 1980 Civil Rights of Institutionalized Persons Act. Although Indiana signed a consent decree promising major reform, long-lasting change proved elusive. Civil and criminal lawsuits proliferated. In 1992, as Central State continued to attract negative attention, Indiana Governor Evan Bayh ordered the troubled hospital closed. His decision promised to save the state millions of dollars and won plaudits from many, but not all, mental health advocates. Even as the last patients left in 1994, some families continued to challenge the wisdom of eliminating Indiana's only large urban mental hospital, but to no effect.